Fertility desire and intention of people living with HIV/AIDS in Tanzania: a call for restructuring care and treatment services - Mmbaga Elia J; Leyna Germana H; Ezekiel Mangi J; Kakoko Deodatus C (BMC, 2013)
Abstract Background Scaling up of antiretroviral therapy (ART) is currently underway in sub-Saharan Africa including, Tanzania, increasing survival of people living with HIV/AIDS (PLWHA). Programmes pay little attention to PLWHA's reproductive health needs. Information on fertility desire and intention would assist in the integration of sexual and reproductive health in routine care and treatment clinics. Methods A cross-sectional study of all PLWHA aged 15-49 residing in Kahe ward in rural Kilimanjaro Tanzania was conducted. Participants were recruited from the community and a local counselling centre located in the ward. Data on socio-demographic, medical and reproductive characteristics were collected through face-to-face interviews. Data were entered and analysed using STATA statistical software. Results A total of 410 PLWHA with a mean age of 34.2 and constituting 264 (64.4%) females participated. Fifty-one per cent reported to be married/cohabiting, 73.9% lived with their partners and 60.5% were sexually active. The rate of unprotected sex was 69.0% with 12.5% of women reporting to be pregnant at the time of the survey. Further biological children were desired by 37.1% of the participants and lifetime fertility intention was 2.4 children. Increased fertility desire was associated with living and having sex with a partner, HIV disclosure, good perceived health status and CD4 count ≥200 cells for both sexes. Reduced desire was associated with havingmore than 2 children among females, divorce or separation, and having a child with the current partner among both males and females. Conclusion Fertility desire and intention of PLWHA was substantially high though lower than that of the general population in Tanzania. Practice of unprotected sexual intercourse with higher pregnancy rate was observed. Fertility desire was determined by individual perceived health and socio-family related factors. With increasing ART coverage and subsequent improved quality of life of PLWHA, these findings underscore the importance of integrating reproductive health services in the routine care and treatment of HIV/AIDS worldwide. The results also highlight a group of PLWHA with potentially high desire for children who need to be targeted during care.